Expansion, Reduction and Correspondence in English Translations of the Poems of Hafiz - Manafi Anari, Salar (Iranian Journal of Translation Studies, 2012)
This research is a contrastive analysis and comparative study of four English translations of some poems of Hafiz in order to find the frequency of lexical expansion, reduction, and correspondence in the translations. The theoretical framework is lexical expansion and reduction proposed by Nida and Taber (1969), but the researcher has also added »lexical correspondence«, as the third strategy, to those two. In analyzing the English translations, the researcher investigated the corpus to see which one of the three strategies is most frequently and which one is least frequently used in the translations. The result shows that lexical expansion is the most frequently used strategy, and lexical reduction is the least frequently used one in the translations studied. The reasons for this result are: firstly, definite and indefinite articles as well as various prepositions are widely used in the English language; secondly, Persian poetry is highly condensed and compact from semantic point of view; therefore, when it is translated into English, it will be in need of being expanded and explained; thirdly, most of the translators are usually inclined to have their translations explicit, free of any ambiguity, and intelligible for the readers.